New challenges in cholangiocarcinoma candidates for elective surgery: harnessing the microbiome dysbiosis - Re, Oriana Lo; López-López, Victor; Balaguer-Román, Andrés; Martínez-Sánchez, María Antonia; Eshmuminov, Dilmurodjon; Llamoza-Torres, Camilo Julio; Miura, Kohei; Baroja-Mazo, Alberto; Ramírez, Pablo; Robles-Campos, Ricardo; Ramos-Molina, Bruno (Langenbeck's archives of surgery, 2023)
BACKGROUND: The gut microbiota, composed by several species of microorganisms, works to preserve the liver-gut homeostasis and plays an important role during digestion and absorption of nutrients, and in the immune response of the host. In this review, we analyzed the influence of microbiota in patients with cholangiocarcinoma (CCA) who were candidates for elective surgery. METHODS: A literature review was conducted to identify papers that provided empiric evidence to support that the altered microbiota composition (dysbiosis) is related also to CCA development. RESULTS: Bacteria such as Helicobacter pylori, Helicobacter hepaticus, and Opisthorchis viverrini increase the risk of CCA. The most abundant genera were Enterococcus, Streptococcus, Bacteroides, Klebsiella, and Pyramidobacter in CCA's biliary microbiota. Additionally, levels of Bacteroides, Geobacillus, Meiothermus, and Anoxybacillus genera were significantly higher. An enrichment of Bifidobacteriaceae, Enterobacteriaceae, and Enterococcaceae families has also been observed in CCA tumor tissue. Microbiota is related to postoperative outcomes in abdominal surgery. The combination of caloric restriction diets in liver cancer or CCA increases the effect of the chemotherapy treatment. CONCLUSION: The correct use of nutrition for microbiota modulation according to each patient's needs could be a therapeutic tool in combination with elective surgery and chemotherapy to diminish side effects and improve prognosis. Further investigations are needed to fully understand the mechanisms by which they are related.
Keywords: Liver cancer; žlučové cesty intrahepatální; Opisthorchiasis; mikrobiota; lidé; cholangiokarcinom; nádory žlučových cest; Dysbiosis; Cholangiocarcinoma; opistorchióza; Microbiota; Diet; Surgery; dysbióza; Bile Duct Neoplasms; Bile Ducts, Intrahepatic; Humans